Danhong injection alleviates OGD-induced blood-brain barrier injury via VEGFR2/PI3K/AKT pathway based on network pharmacology and experimental evidence - Yutong Zhang; Meixia Xie; Jiayin Liang; Li Li; Shumei Wang; Minghua Xian (KeAi Communications Co., Ltd., 2024)
Objective: Previous studies have shown that Danhong injection (DHI) has a protective effect on the blood-brain barrier (BBB) function after ischemic stroke. However, the role of DHI in protecting the integrity of the BBB after ischemic stroke through endothelial cells is still unclear. The purpose of this study is to explore the role and mechanism of DHI in protecting BBB by interfering with endothelial cells. Methods: We used network pharmacology technology to determine the potential pathways and mechanisms of DHI in treating ischemic stroke through endothelial cells. On account of the network pharmacology results, we assessed the effects of DHI in oxygen-glucose deprivation (OGD) model of mouse brain-derived endothelial (bEnd.3) cells via MTT, and validated the molecular mechanisms of DHI improving BBB injury through Western blot. Results: Network pharmacology analysis suggested that DHI may regulate the PI3K/AKT signaling pathway of endothelial cells in the treatment of ischemic stroke. Cellular experiments showed that DHI stimulates endothelial cell migration and reduces OGD-induced BBB damage via VEGFR2/PI3K/AKT pathway. Conclusion: Network pharmacology analysis and cellular experiments have shown that DHI alleviated the BBB damage by activating the VEGFR2/PI3K/AKT signaling pathway on endothelial cells.